2007
DOI: 10.1124/dmd.107.017871
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, Disposition, and Metabolism of Bicifadine in Humans

Abstract: ABSTRACT:Bicifadine [DOV 220,075; (؎)-1-(4-methylphenyl)-3-azabicyclo-[3.1.0]hexane HCl)] is a non-narcotic analgesic that has proven to be effective for the treatment of acute pain in clinical studies. The pharmacokinetics, disposition, and metabolism of bicifadine were determined in eight healthy adult male subjects following a single oral dose of 200 mg of [ 14 C]bicifadine in solution. The maximum concentration of total drug equivalents and bicifadine in plasma was at approximately 1 h; the elimination hal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 10 publications
0
20
0
1
Order By: Relevance
“…Bicifadine (Fig. 11) is a potent inhibitor of SERT and NET and is currently in development against neuropathic pain (Krieter et al, 2008). It is noteworthy that bicifadine also possess inhibitory activity against DAT (Basile et al, 2007), which indicates that inhibition of all three monoamine transporters might provide a novel and efficacious strategy for the treatment of neuropathic pain.…”
mentioning
confidence: 99%
“…Bicifadine (Fig. 11) is a potent inhibitor of SERT and NET and is currently in development against neuropathic pain (Krieter et al, 2008). It is noteworthy that bicifadine also possess inhibitory activity against DAT (Basile et al, 2007), which indicates that inhibition of all three monoamine transporters might provide a novel and efficacious strategy for the treatment of neuropathic pain.…”
mentioning
confidence: 99%
“…Several open-label randomized controlled clinical trials, meta-analyses, and systematic reviews have confirmed the clinical efficacy of selected antidepressants in persistent pain conditions (Dharmshaktu et al, 2011). Clinical studies have corroborated that bicifadine is an effective analgesic in the treatment of postoperative pain (Krieter et al, 2008). In a second study, the TRI NS7051, has shown comparable antinociceptive properties to tramadol confirming the interest of these antidepressants in the relief of pain (Munro et al, 2008).…”
Section: Clinical Properties Of Trismentioning
confidence: 75%
“…Mechanical hyperalgesia was also reduced by bicifadine in the STZ model of neuropathic pain (Basile et al, 2007). Clinical (phase II/III) studies have demonstrated that bicifadine is an effective analgesic in the treatment of postoperative pain (Krieter et al, 2008). The impact of bicifadine on 5-HT, NE and DA neurotransmissions was confirmed by in vitro binding assays and intracerebral in vivo microdialysis study in freely moving rats.…”
Section: Pain Relief By Tris An Example Of Symptom Of Depressionmentioning
confidence: 86%